Evaluation of the reproducibility of the Tronzo classification for intertrochanteric fractures of the femur in an orthopedic service of a Hospital in Ibagué, Colombia.: Evaluación de la reproducibilidad de la clasificación de Tronzo para fracturas intertrocantéricas de fémur en un servicio de ortopedia de un Hospital de Ibague, Colombia. - Valencia, Paula A. (2022)
Introduction: Hip fractures are a pathology of traumatic origin that generates a high impact on public health. The objective is to evaluate the interobserver reproducibility of the Tronzo classification for intertrochanteric fractures. Methods: Observational, analytical and retrospective study carried out in Ibagué - Colombia, 48 hip radiographs were analyzed, classified by 10 observed among specialists and training personnel, using the Tronzo classification. Interobserver reproducibility is assessed using the kappa concordance coefficient. Results: Among all those observed in the study, there is greater agreement in the identification of intertrochanteric fractures of lesser and greater severity (Tronzo I and V), the main exponents of this agreement are the most experienced staff, the staff in training, with intermediate experience they agree when identifying those of intermediate severity and for those with less experience the concordance becomes evident when evaluating the intermediate grades. Conclusion: The concordance increases with the experience for the identification of the types with high complexity. This classification is not suitable for clinical practice, another system is necessary for this type of fracture in clinical conduct.